Distinguished artistic productions and their relationship to some personal characteristics of year students Fourth Department of Art Education (Journal of the College of Basic Education, 2023)
All developed countries have sought to create an educational climate that helps the student in the upbringing and development ofhis creative ability, in that “creative programs lead to an increase in creative ideas asAnd how, it also leads to a change in personality traits, such as the tendency to self-reliance and confidence.It has the ability to persuade, initiate, lead and direct others (29, p. 20).In addition to paying attention to the nature and personality of the student and making him the focus of the educational process.Interacting with other elements and surrounding environmental conditions by providing learning opportunitiesextensive use of modern educational theories and theories of communication, in order to push him to search forDistinguished new ideas capable of meeting the requirements of the modern era, as well as the great interest thatThe higher education institutions attach these creative energies and the great role they play inScientific Progress Service, where educational institutions have devoted themselves to developing their academic curricula.and improving its teaching methods in an effort to nurture the creative and distinguished abilities of the learners.A lot of literature indicates the possibility of breeding and developing these abilities through regulating the conditions in whichexperienced by the learner, and “Qeladah” believes that the mental abilities employed in discovery and invention are consideredShe has high mental abilities and needs basic abilities to be developed in the arena of teaching and learning. ,15)p. (199